2011
DOI: 10.1080/10889868.2011.624139
|View full text |Cite
|
Sign up to set email alerts
|

The Suitability of Jatropha Seed Press Cake as a Biosorbent for Removal of Hexavalent Chromium from Aqueous Solutions

Abstract: Jatropha seed press cake (JPC), a biodeisel waste, was investigated for its use as biosorbent for Cr(VI) removal from wastewater. The acid-pretreated biomass exhibited 1.9-fold higher biosorption efficiency for Cr(VI). The Cr(VI) biosorption efficiency was found to increase with decrease in pH of aqueous medium. The adsorption capacity of biosorbent for Cr(VI) increased with increasing concentration of Cr(VI). The biosorption of Cr(VI) by acid-treated JPC followed a pseudo-second-order kinetics. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…5C) was in good agreement with the pseudo-second-order kinetic model as the regression coefficient (R 2 ) was more close to unity for all the different concentration used. Similar results was also reported by Bose et al (2011) and Mondal et al (2017) using Jatropha seed press cake and A. niger, respectively.…”
supporting
confidence: 91%
“…5C) was in good agreement with the pseudo-second-order kinetic model as the regression coefficient (R 2 ) was more close to unity for all the different concentration used. Similar results was also reported by Bose et al (2011) and Mondal et al (2017) using Jatropha seed press cake and A. niger, respectively.…”
supporting
confidence: 91%
“…According to the authors, the equilibrium time and optimum pH range were observed to be 3 h and 4.0-6.0, respectively. SCSC exhibit a higher adsorption capacity of 115.86 mg/g than commercial activated carbon (21.69 mg/ g) at 300 K. Bose et al (2011) evaluated a biodiesel waste of jatropha seed press cake (JPC) for the elimination of hexavalent chromium ion from aqueous solutions. The chromium metal removal increases with increase in pH as well as concentration.…”
Section: Cakementioning
confidence: 99%
“…The linearity of plots revealed that the adsorption followed Langmuir isotherm model. The Langmuir parameter, Q m values obtained in this work were compared with the results reported in literature [56][57][58][59][60] ( Table 3). The essential characteristic of the Langmuir isotherm can also be evaluated by dimensionless adsorption intensity R L given by [61]:…”
Section: Langmuir Isotherm Modelmentioning
confidence: 84%